Speaking Anxiety in the Virtual English Classroom - Lisa Rakhmanina; Melati, Melati (Corolla International Conference, 2023)
This study explored the anxiety that students in English classes at the Faculty of Economy and Business at Universitas Prof. Dr. Hazairin SH experience when they have to speak in front of their peers. The goal of this research is to investigate both the factors that contribute to students' anxiety about public speaking as well as the ramifications of that fear. Undergraduate students from the Faculty of Economy and Business who were enrolled in an English class during the academic year 2022/2023 were eligible to participate in the study. Participants were selected at random. Out of a total of 210 students, there were 85 students chosen at random to participate in the study. The researchers used both questionnaires and interviews to obtain their data for this study. According to the findings, the vast majority of students experience substantial levels of anxiety when it comes to giving presentations in front of an audience. The interview also revealed that the students' worry was caused by a lack of vocabulary, challenges with confidence, fear of making errors, and shyness. All of these factors contributed to the students' anxiety.